Strategi Manajemen Sumber Daya Manusia dalam Menghadapi Perubahan Satuan Organisasi TNI-AD di Koramil 05 Rungkut Surabaya - Muncahyo, Wawan (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2024)
This study aims to analyze human resource management strategies in dealing with organizational unit changes at Koramil 05 Rungkut Surabaya. This study uses a qualitative approach with a case study method to analyze human resource management (HR) strategies in dealing with organizational changes at Koramil 05 Rungkut Surabaya. Data were collected through in-depth interviews, participant observation, and documentation, focusing on the role of the Koramil Commander, personnel, and HR staff. Data analysis was carried out through a coding process, thematic analysis, and triangulation to ensure the validity of the findings related to the impact of restructuring on personnel performance and motivation. This study analyzes human resource management (HR) strategies at Koramil 05 Rungkut Surabaya in dealing with organizational structure changes due to restructuring. The findings show that role adjustment, HR management, technology adaptation, and increased motivation and coordination are very important to maintain operational performance. HR training and development are the keys to the success of personnel adaptation to new challenges, especially in mastering technology and increasing collaboration between units. Internal conflicts that arise can be managed well through open communication and active participation of all personnel.